Impact of Self Management on Quality of Life Among Hemodialysis Patients : A Scoping Review - Alya, Syafika Putri; Armiyati, Yunie; Mubin, Mohammad Fatkhul (Media Keperawatan Indonesia, 2025)
Chronic Kidney Disease (CKD) is a progressive and irreversible kidney function disorder, characterized by a glomerular filtration rate of <15 ml/minute/1.73 m², thus affecting an individual's health and quality of life. Therefore, it is important to examine the effect of self-management on quality of life in chronic kidney disease patients undergoing hemodialysis. Researchers conducted a systematic review of the quality of life of kidney failure patients undergoing dialysis. This scoping review aims to determine the effect of self-management on improving quality of life. This systematic review uses the PICOS framework method to search for articles in databases such as ScienceDirect, PubMed, and Google Scholar. The articles used were 10 articles with a time period of 2020-2024, and the type of research used was randomized controlled trial and quasi-experimental. The results of the study showed that the self-management scale and quality of life before the intervention were low, while the intensity after the intervention was given was good. Self-management has a positive influence on improving the quality of life scale in chronic kidney disease patients undergoing hemodialysis based on the concept of cognitive behavior. It is hoped that self-management can be a recommendation in services at health facilities to improve the health status of chronic kidney disease patients undergoing hemodialysis.